How to begin studying English literature - Marsh, Nicholas, 1948- (Macmillan, 1995)
This revised edition offers help and guidance to students and sets out a method for approaching novels, plays and poems. There are chapters on themes, characters, structure and style, and advice on writing essays and how to set about revision.